Electrochemiluminescence Immunosensor Based on Platinum Electrode Modified with TiO2@ATO Nanocomposite for Sensitive Detection of AFB1. Issue 16 (1st January 2019) - Cheng, Shuting; Chu, Guanglei; Liu, Zengning; Guo, Yemin; Sun, Xia
Abstract : A novel electrochemiluminescence (ECL) immunosensor was fabricated by using titanium dioxide (TiO2 ) and antimony tin oxide (ATO) nanocomposite as electrode modified material to detect aflatoxin B1 (AFB1 ). Luminol with ECL characteristics was modified on the surface of a platinum electrode to prepare the luminescent electrode. The buffer solution contained hydrogen peroxide (H2 O2 ) was used to monitor the ECL signals owing to the chemiluminescence properties of luminol-H2 O2 in alkaline solution. TiO2 and ATO were doped with chitosan to form TiO2 @ATO nanocomposite, which was modified on the electrode to enhance the ECL intensity by accelerating the electron transfer and provided more binding sites for aflatoxin B1 antibody (Ab) and AFB1 . An ECL immunosensor was prepared for AFB1 detection by modifying Ab and bovine serum albumin (BSA) successively. The specific combination of AFB1 and Ab weakened the ECL intensity, thus the concentration of AFB1 was determined according to the strength change of ECL signal. Under optimum conditions, the constructed immunosensor provided a wide linear range from 1.0 × 10 −2 to 1.0 × 10 3 ng mL −1 with a detection limit of 0.03 ng mL −1 (S/N = 3) and showed great specificity and high stability. Furthermore, the proposed immunosensor successfully demonstrated its applicability for detecting AFB1 in peanut oil samples.